A Plasmon Resonance Enhanced Photo‐Electrode to Promote NH3 Yield in Sustainable N2 Conversion. Issue 25 (20th March 2023) - Wang, Haonan; Cheng, Chuanqi; Du, Kun; Xu, Zongwei; Zhao, Erling; Lan, Ning; Yin, Peng‐Fei; Ling, Tao
Abstract: A key challenge for electrochemical nitrogen reduction reactions (NRR) is the difficulty for conventional catalysts to achieve high currents at low H* coverage to produce appreciable NH3 . Herein, we specially designed an Au nanoparticle‐embedded ZnSe photo‐electrode to solve the problem. As‐designed photo‐electrode achieves excellent NRR performance with a high NH3 yield (12.2 μg cm −2 h −1 ) and Faradaic efficiency (27.3 %). Our work reveals that the unique plasmon resonance effect of embedded Au nanoparticles plays a key role in increasing catalytic current when the H* coverage is decreased. Moreover, we successfully established a correlation between H* coverage and NRR performance based on theoretical calculations and experimental observations. This work paves the path for the future design of catalytic materials to overcome the selectivity and yield challenge of sustainable NH3 production. Abstract : A strategy is proposed to address current NH3 yield challenge of NRR by achieving low H* coverages at appreciable current densities based on the unique SPR effect and established a correlation between H* coverage and NRR performance. The specifically designed ZnSe(Au) electrode achieves a high FE and NH3 yield rate of 27.3 % and 12.2 μg cm −2 h −1, respectively.